Virtuality of Seno Gumira Ajidarma’s Eyewitness as a work of magical realism - Faruk Faruk (Penerbit Universiti Kebangsaan Malaysia, 2024)
In the authoritarian regime of the New Order (NO), news regarding Indonesian colonization and massacres towards East Timor could not be openly published. Seno Gumira Ajidarma who is actually a journalist had to convey his testimony through literary media instead of journalist report, particularly in the short stories collected in Saksi Mata (SM) (Eyewitness). The inquiry centers on the question: by what narrative strategy does Ajidarma convey the testimony? Since it is apparent that he uses magic realism technique to tell the stories. This raises the question of how the global genre made to be relevant to national political issue. This paper focuses on the strategy used by Ajidarma to communicate what could not be openly expressed, along with its ideological implications. By applying Aldea’s virtuality theory of Magic Realism, which is based on Deleuzian ontology, this research finds that the short stories in SM employ magical realism virtuality to solve the problem of expression that is repressed by the NO. This enables them to achieve both relative and absolute deterritorialization of the knowledge system controlled by the NO regime in East Timor. Relative deterritorialization is conducted by transforming the identity of the narrator character to a narrator that transcends the boundaries of NO identification, while absolute deterritorialization is conducted by linking the characters directly to the abstract creative power of Being through the “flute art” that continually to move without sound and words, dragging and displacing all categories of the actual world.